OPTIMASI PENEMPATAN KAPASITOR BANK UNTUK PERBAIKAN RUGI DAYA PADA PENYULANG SABA MENGGUNAKAN ALGORITMA GENETIKA - I. K. A. Wijaya; R. S. Hartati; I W. Sukerayasa (Jurnal SPEKTRUM, 2019)
Saba feeder is a feeder who supplies 78 distribution transformers with feeder length 38,959 kms, through this Saba feeder electrical energy is channeled radially to each distribution substation. In 2017 the voltage shrinkage at Saba feeder was 9.88% (18,024 kV) while the total power loss was 445.5 kW. In this study an attempt was made to overcome the voltage losses and power losses using the method of optimizing bank capacitors with genetic algorithms and network reconfiguration. The best solution obtained from this study will be selected for repair of voltage losses and power losses in Saba feeders. The results showed that by optimizing bank capacitors using genetic algorithms, the placement of capacitor banks was placed on bus 23 (the channel leading to the BB0024 transformer) and successfully reduced the power loss to 331.7 kW. The network reconfiguration succeeded in fixing the voltage on the Saba feeder with a voltage drop of 4.75% and a total power loss of 182.7 kW. With the combined method, reconfiguration and optimization of bank capacitors with genetic algorithms were obtained on bus 27 (channel to transformer BB0047) and managed to reduce power losses to 143 kW.